A numerical analysis of various pH level for fiber optic pH sensor based on bromophenol blue in silica / M. Zolkapli ...[et al.] - Zolkapli, M.; Saharudin, S.; Herman, S. H.; Abdullah, W. F. H. (UiTM Press, 2016)
The fabrication and characterization of an optical fiber pH sensor for the detection range 2 – 7 are described. The sensing element was prepared by coating the uncladded middle portion of a multimode plastic clad silica fiber (PCF) with xerogel film of immobilized bromophenol blue (BPB) prepared by a solgel process. The exponential decay of the evanescent wave at the core-cladding interface of the multimode fiber was utilized to determine the pH response. The objective of this work is to analyze the measurement of the fiber optic sensing probe towards various pH level. The intensity of the absorbance was analyzed using statistical technique (Statistical Package for the Social Sciences, SPSS) to identify the significant pH range that can be used as a reference in developing the sensor instrumentation in the future. pH2 shows the highest significance among all pH values based on the statistical results using error plots.